A successful case study of using HCl and viscoelastic diverting acid systems for carbonate matrix acidizing in an oil well with optimized predictive model - Javad Mahdavi Kalatehno; Ehsan Khamehchi; Mostafa Keihanikamal; Fatemeh Yousefmarzi; Matin Dargi; Peyman Daneshfar (Journal of Petroleum Exploration and Production Technology)
Abstract The oil and gas industry is continuously seeking advanced methods to optimize reservoir productivity. Among the techniques employed, matrix acidizing, particularly using Viscoelastic Diverting Acid (VDA), has shown significant promise in enhancing permeability and improving well performance. However, the absence of standardized formulations for VDA requires a careful evaluation of commercial additives to ensure their reliability and effectiveness in diverse reservoir conditions. This article presents a comprehensive case study that examining the application of hydrochloric acid (HCl) and VDA systems in a low-permeability carbonate reservoir situated in southern Iran. The study integrates design of experiments (DOE) and multi-objective optimization techniques to assess the impact of various operational parameters on acidizing performance. The research focused on high-temperature formations, employing multi-stage acid injections to evaluate the effectiveness of the acid treatments. The use of DoE and response surface methodology (RSM) provided a structured approach for optimizing key parameters to enhance treatment outcomes. The results of this study demonstrated a substantial increase in both oil production and well pressure following the acidizing process. Specifically, oil production improved by 80%, and well pressure increased by 73%, underscoring the effectiveness of the acid treatment in stimulating the reservoir. The VDA system, combined with the bullheading injection technique, facilitated superior acid placement and distribution within the reservoir, enhancing the overall acidizing efficiency. Furthermore, the optimization of operational parameters such as skin factor and maximum invasion depth through the use of RSM allowed for a significant refinement of the acidizing process. The developed models, with correlation coefficients exceeding 0.96, further validated the accuracy of the optimization process and provided valuable insights into the critical factors influencing acidizing performance. Additionally, the refined acidizing program minimized operational uncertainties, leading to improved treatment efficiency and more consistent results in challenging high-temperature formations.